Adsorption of tetracyclines onto polyethylene microplastics: A combined study of experiment and molecular dynamics simulation. (February 2021) - Chen, Yajun; Li, Jining; Wang, Fenghe; Yang, Hao; Liu, Lei
Abstract: Microplastics are a kind of new organic pollutant in the environment. In this study, the adsorption of tetracyclines (TCs), including tetracycline hydrochloride (TC), chlortetracycline hydrochloride (CTC) and oxytetracycline hydrochloride (OTC) onto polyethylene (PE) microplastics in aqueous solutions were investigated. The mechanism of the adsorption behavior was preliminarily explored by adsorption kinetics, isotherms, and thermodynamics, in combination with scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS). In addition, molecular dynamics (MD) simulation was applied to investigate the adsorption processes of TCs on PE at a molecular level. It was found that the adsorption behaviors of TCs reached an equilibrium state within 30 h. The experimental data showed that adsorption capacities of TCs onto PE were as follows: OTC (64.40 ± 2.38 μg/g)>CTC (63.36 ± 4.92 μg/g)>TC (53.52 ± 3.43 μg/g). TC sorption onto PE increased with pH, peaking at around pH 6 and then decreased. The increase of ionic strength in the solution led to the reduced adsorption capacity of TC onto PE. The results indicated that the experimental data were well fitted by the pseudo-second-order model and the Freundlich isotherm model, indicating both monolayer and multilayer coverage of TCs onto the surface of PE. The results of MD simulation showed that PE can effectively adsorb the TCs molecule mainly through non-bond interactions, and PE exhibited the highest affinity for CTC and OTC, followed by TC. Graphical abstract: Image 1 Highlights: TCs adsorption on PE microplastics investigated by experiments and molecular dynamics simulation. TCs adsorption onto PE fitted well with Freundlich and pseudo-second-order model. TCs adsorption onto PE could be influenced by pH and salinity. TCs adsorption onto PE was mainly controlled by intermolecular van der Waals force.